EXPRESSION OF CONFLICT, SYNONYMY AND SIMILARITY IN ARTICLES - Kholmatova Odinakhan Uktamovna (Western European Studies, 2025)
In this article, information about the expression of synonymy, antonymy and similitude in proverbs is given and analyzed with examples. It can be said that the compact size of the proverb allows to use lexical homonyms in it. In addition, in the semantics of proverbs, rather than puzzling word games, it is possible to evaluate the expression of meaningful and meaningful words and sentences as an important requirement of proverb semantics. All this shows the unique aspects of paremic units known as proverbs
Keywords: lexical homonym; semantics; dialect